2020
DOI: 10.1042/bsr20193760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-rays on transcript expression of rat brain microvascular endothelial cells: role of calcium signaling in X-ray-induced endothelium damage

Abstract: Radiation-induced brain edema is a serious adverse effect of radiotherapy. Although there are many causes of radiation-induced brain edema, the pathogenesis is not clear and clinical treatment is not ideal. Therefore, knowing the differential expression of the brain microvascular endothelial cell (BMEC) transcriptome after brain radiotherapy may shed light on the pathogenesis of radiation-induced brain edema. The present study used RNA-Seq technique to identify 383 BMEC transcripts differentially expressed (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…However, how the underlying mechanisms of endothelial dysfunction and endothelial function change over time and with dose of radiation remain unclear. We previously investigated the effect of a delivered x-ray dose of 20 Gy on transcript expression in BMECs by using high-throughput sequencing ( Wu et al, 2020 ), a powerful tool for revealing changed genetic patterns and potential therapeutic targets of disease ( Ma et al, 2010 ; Azorsa et al, 2016 ). The present study followed up on that work and further explored transcript expression alterations with two doses (5 Gy or 20 Gy) and times (12 h or 24 h) following x-ray exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, how the underlying mechanisms of endothelial dysfunction and endothelial function change over time and with dose of radiation remain unclear. We previously investigated the effect of a delivered x-ray dose of 20 Gy on transcript expression in BMECs by using high-throughput sequencing ( Wu et al, 2020 ), a powerful tool for revealing changed genetic patterns and potential therapeutic targets of disease ( Ma et al, 2010 ; Azorsa et al, 2016 ). The present study followed up on that work and further explored transcript expression alterations with two doses (5 Gy or 20 Gy) and times (12 h or 24 h) following x-ray exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, such data assessing the molecular mechanisms of radiation-induced vascular dysfunction are insufficient and incomplete. A recent study by our team analyzed x-ray–treated (20 Gy) brain microvascular endothelial cells (BMECs) with next-generation sequencing and found that this radiation causes 383 genes to be significantly differentially expressed in BMECs and that these genetic alterations are accompanied by functional changes in the calcium (Ca 2+ ) signaling pathway ( Wu et al, 2020 ). In the present study, we used next-generation sequencing to further investigate the effects of two delivered doses of ionizing radiation (5 and 20 Gy) and of time after the exposure on transcriptional expression changes in BMECs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell death, proliferation and clonogenic ability are affected by irradiation depending on the dose delivered and the characteristics of the beam. Irradiation-related apoptosis was the most studied effect (43/147 studies, 29.3%), mainly measured through immunofluorescence staining ( Figure 4 a) or flow cytometry [ 13 , 16 , 23 , 30 , 32 , 46 , 61 , 63 , 66 , 68 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. The causal link between IR and apoptosis in ECs has been investigated for years, with examples going back to 25 years ago [ 103 ].…”
Section: Analyzing Resultsmentioning
confidence: 99%
“…Our team recently used next-generation sequencing to explore changes in the transcription profile of rat brain microvascular endothelial cells (rBMECs) after radiation exposure [ 8 ]. We found that calcium (Ca 2+ ) signals including 38 genes were significantly changed.…”
Section: Introductionmentioning
confidence: 99%